Kemelimpahan dan Karakterisasi Bakteri Rizosfer Tanaman Kelapa Sawit di PT Bumitama Gunajaya Agro Kalimantan Tengah - Ridho Asmara; Radix Suharjo; Maria Rini; Suskandini Ratih Dirmawati (Journal of Tropical Upland Resources (J. Trop. Upland Res.), 2021)
. The palm oil (Elaeis guineensis Jacq.) is the one of  main plantation crops industry in Indonesia.  The production of  palm oil in Indonesia still be optimized, however  there is numerous obstacles , which is Ganoderma Boninensea fungus that caused of stem rotten disease. The ability of G. boninense  to  infected palm oil plant was greatly influenced by abundance and diversity of bacteria that found in the rhizospher area. This research aims to know abundace and characterization of bacteria in rhizospher palm oil in several locations in PT Bumitama Agro Gunajaya , Central of Kalimanan. The observation  was done by counting the number of populations of bacteria and by distinguished on the basis of form and colors.  The oxidative fermentative gram (O/F)  test, softrot test, hypo virulent test and hypersensitive were as additional test. The results of the study showed that many of 161 bacteria isolates obtained by the number of different bacterial populations. The highest population numbers obtained in the territory with a PAGE ultisol soil type was 15998.4 X 104 CFU/g soil and the lowest population  numbers in the territory PAGE with histosol soil type was 7332.6 X 104 CFU/g soil. The form of the bacterial colony morphology obtained was rounded and  irregular colonies with the color red, white, pink, yellow and white turbid.  Most of bacteria were 58.8% Gram-positive, 82% fermentative, 63.4% reacted overwhelmingly negative in hypersensitive test, 80.1% negative in softrot and 91.2% was hypovirulen.